EFFECT OF INTERNAL AUDIT QUALITY ON THE EFFECTIVENESS OF GOOD CORPORATE GOVERNANCE (CASE STUDY AT PT JASA RAHARJA): Internal Audit Quality (Independence, Professional Capability, Scope of Work, Examination), Good Corporate Governance - Arya Adhitya Putra, Fajar; Mulya, Hadri (Dinasti Publisher, 2020)
This study aims to examine the Effect of Internal Audit Quality on the Effectiveness of Good Corporate Governance which is seen from the Independence of Auditors, Professional Capabilities, Scope of Work and Examination at PT Jasa Raharja.The population in this study were all employees of PT Jasa Raharja which were divided into Employees of the Internal Control Unit, Head of Branches, Head of Division, Head of Internal Control Unit and Corporate Secretary of PT Jasa Raharja. Samples obtained by purposive sampling method were as many as 85 employees. The results of statistical tests show that the Quality of Internal Audit has a significant effect on the Effectiveness of Good Corporate Governance that is measured using variables such as Independence, Professional Capability, Scope of Work and Examination.